1992
DOI: 10.1111/j.1525-1470.1992.tb00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypomelanosis of Ito: Diagnostic Criteria and Report of 41 Cases

Abstract: We conducted a 20-year prospective review of 41 pediatric patients with a diagnosis of hypomelanosis of Ito. No evidence pointed to hereditary transmission of the disease. Associated extracutaneous pathology was mainly of the nervous and musculoskeletal systems. Three of 19 patients had chromosomal anomalies. Hypomelanosis of Ito is a clinically well-characterized syndrome in which chromosomal instability may be a component. Criteria for its presumptive and definitive diagnosis are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0
5

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(113 citation statements)
references
References 39 publications
1
102
0
5
Order By: Relevance
“…In 1967, Hamada et al confirmed the association between skin lesions and systemic abnormalities, including mental retardation. RuizMaldonado et al proposed diagnostic criteria in 1992 [3]. We report two patients with this disorder.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…In 1967, Hamada et al confirmed the association between skin lesions and systemic abnormalities, including mental retardation. RuizMaldonado et al proposed diagnostic criteria in 1992 [3]. We report two patients with this disorder.…”
Section: Introductionmentioning
confidence: 79%
“…Some believe HOI is related to autosomal dominant inheritance [8] and others attribute it to chromosome instability and mosaicism [3]. Chromosomal abnormalities, particularly translocation and mosaicism have been reported in approximately 50% of cases [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A HI é uma síndrome clínica bem caracterizada na qual a instabilidade cromossômica pode ser um componente 13,14 . Anomalias cromossômicas, especialmente translocações ou mosaicismo, são encontradas em aproximadamente 50% dos casos 7 ; isso sustenta a hipótese de que o padrão é o resultado da migração de dois clones de melanó-citos primordiais, cada um com diferente potencial de pigmentação.…”
Section: Comentáriosunclassified
“…HI is a well-defined entity in the dermatologic literature (2,5) and is thought to be one of the neurocutaneous syndroms because it is often associated with seizures and mental retardation (3,4). Although short stature is sometimes associated with HI, the cause has not been studied.…”
Section: Case Reportmentioning
confidence: 99%